Effect of diamond bur cutting efficacy on dentin bond strengths of different bonding systems - Shirani F.; Malekipour M.; Shahabi H. (Tehran University of Medical Sciences, 2009)
"nBackground and Aim: As composite-dentin bond strength is affected by cavity preparation and the bond strength of composite resin to new and used bur prepared dentin has not yet been evaluated, this study evaluated the effects of cutting dentin with different cutting efficacy (new and used) of burs on composite-dentin shear bond strength using self-etching primer bonding system and total etching bonding system. "nMaterials and Methods: Sixty caries free human 3rd molar were sectioned in occlosal surface to expose dentin, then polished with silicon carbide paper and randomly divided into four groups. Each group was prepared in a depth of 0.5mm of dentin, using new diamond bur, or used diamond bur. To change into a used bur, each new rough diamond bur had to work on bovine enamel for 30 minutes, under a load of 150g. Then, each group was bonded, using a total etch adhesive (single Bond) or a self etch adhesive (clearfil SE Bond) So there were 4 groups : 1-SE Bond, New bur; 2-SE Bond , used bur; 3-Single Bond , New bur ; 4-Single Bond, used bur. Similar composite capsules(Filtek Z250) were bonded to dentin surface and cured. specimens were stored in physiologic saline for 48h at 370 c , then put under shearing load to define composite - dentin shear bond strength. Results were interpreted via statistical analysis (T-test & two - way variance). "nResults: Shear bond strength of each group was as follows: 1-(27.3Mpa), 2-(33.5Mpa), 3-(16.9Mpa) 4-(19.3Mpa). Statistical analysis proved that shear bond strength of used diamond bur prepared groups (2,4) was more than new diamond bur prepared ones (1,3). This statistical difference, specially, was seen between SE Bond groups (1,2) but not between single Bond groups (3,4). Also, shear bond strength of (SE Bond) bonded groups (1,2) were more significantly than (single Bond) bonded ones (3,4). "nConclusion: This study show that Bur cutting efficiency influences composite - dentin shear bond strength especially when the adhesive is SE Bond (used bur> new bur) Also type of adhesive affects on composite - dentin shear bond strength. (SE Bond > Single Bond).